The taxonomic and nomenclatural status of the nomen Anabates pulvericolor Sclater, 1858 (Aves: Furnariidae), with a neotype designation - Stopiglia, Renata; Dubois, Alain; Bockmann, Flávio A.; Raposo, Marcos A. (Zootaxa, 2019)
Different authors have suggested that Anabates pulvericolor Sclater, 1858 might be the valid nomen for Synallaxis propinqua Pelzeln, 1859 or for Synallaxis gujanensis huallagae Cory, 1919. However, due to doubts regarding the taxonomic identity of Anabates pulvericolor Sclater, 1858, of which the unique type is lost, neither of these nomina has been displaced by the senior nomen pulvericolor. Our analysis of the case reveals that Anabates pulvericolor Sclater, 1858 is correctly identifiable with Synallaxis gujanensis huallagae Cory, 1919, of which it is a senior subjective synonym. According to the Code, the senior subjective synonym Synallaxis gujanensis pulvericolor (Sclater, 1858) should be adopted. Given the fact that the holotype of Anabates pulvericolor Sclater, 1858 is missing and that it has been impossible to identify it from its description until now, we designate a neotype from“Río Napo, Ecuador”, its original type locality.